Pengaruh Lama Penyimpanan Telur Herbal Ayam Ras Herbal pada Refrigerator terhadap Penurunan Berat Telur, Diameter Rongga Udara, dan Indeks Kuning Telur - Nugraha, Yoga Indra; Nova, Khaira; Septinova, Dian; Riyanti, Rr (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2025)
This research aims to: (1) determine the effect of storage time in the refrigerator on egg weight loss, air cavity diameter, and yolk index of herbal chicken eggs, (2) determine the storage time that can maintain the quality of herbal chicken eggs in the refrigerator. This research was conducted out on January--March 2024, located in Kampung Baru, Kedaton, Bandar Lampung as a place to store eggs during research and the Animal Production Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The research material used 100 of herbal chicken eggs with an average weight of 58,6±3,97 g from second phase Isa Brown strain chickens (72 weeks old). The research was carried out using a Completely Randomized Design (CRD) experiment consisting of 4 treatments including 0, 12, 24, 36 days of storage and 5 replications. Each experimental unit consists of 5 eggs. The data obtained was analyzed based on Analysis of Variance at a real level of 5%. Results that have a real effect are further tested using the Least Significant Difference (BNT) test. The results of the study showed that the treatment of storage time herbal chicken eggs in the refrigerator had a significant effect (P<0.05) on reducing egg weight, air cavity diameter and yolk index of herbal chicken eggs. The conclusion of this research is that a storage time on 24 days has the best effect on egg weight loss (1.95%), air cavity diameter (22.1mm), and egg yolk index value (0.39) compared to storage periods of 24 and 36 days.